COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH TOWARDS SPEAKING ABILITY - Molla, Nur Laila (LPPM Universitas Pancasakti Tegal, 2018)
Communicative  Language  Teaching  (CLT)  is  a  way  to  deal  with  the  educating  of  second  and  unknown  dialects  that  emphasis  on  cooperation  as  both  the  methods  and  the  last  objective  of  learning  a  language.  Targets  are  (1)  to  discover  Effectiveness  of  CLT  Approach  in  Improving  Speaking  Ability.  (2)  huge  contrasts  between  students  who  are  instructed  by  CLT  and   not.  Quantitative  research  is  a  true  design  experiment.  Design  used  was  a  pretest-posttest  control  group  design.  Population  is  eighth  grader  students  in  Junior  High  School  1  Tegal.  Research  uses  cluster  random  sampling  with  two  group  design  (experiment  group  and  control  group).  Data  was  broke  down  utilizing  a  t-test,  score  of  the  t-test  is  2.744.  Score  of  t-table  is  at  5%  level  importance  and  on  level  of  62  is  1.670,  t-test  result  is  higher  than  t-table  (2.744>1.670).  t-test  hypothesis  is  rejected,  and  t-table  hypothesis  is  accepted.  CLT  improve  speaking  capability.